2018
DOI: 10.1088/1741-4326/aae397
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of tungsten on CFETR phase I performance

Abstract: An integrated modeling workflow using OMFIT is constructed to evaluate the effects of tungsten (W) impurity on China Fusion Engineering Test Reactor (CFETR) performance. Self-consistent modeling of W core density profile, accounting for both turbulent and neoclassical transport contributions, is performed based on the steady-state scenario of CFETR phase I (Wan et al 2016 IAEA; Wan et al 2017 Nucl. Fusion 57 102009). It is found that the fusion performance degrades mildly with increasing W concentration. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Since electron particle transport can be driven not only by normalized electron density gradient a/L ne , but also by coupling with the energy transport channel, we cannot use a simple form like (equation 1) to represent turbulent electron particle flux. The following more representative equation for electron particle flux is used [38]: (5) In this equation, positive Γ means outward particle flux, D Te and D Ti are non-diagonal turbulent electron particle transport coefficients related to a/L Te and a/L Ti respectively, while the 'residual' term, which is composed of the roto-diffusion term and other pure pinch terms, will be left out of our discussion. According to this equation, some important information can be obtained through scan over the normalized 5.…”
Section: Foot Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since electron particle transport can be driven not only by normalized electron density gradient a/L ne , but also by coupling with the energy transport channel, we cannot use a simple form like (equation 1) to represent turbulent electron particle flux. The following more representative equation for electron particle flux is used [38]: (5) In this equation, positive Γ means outward particle flux, D Te and D Ti are non-diagonal turbulent electron particle transport coefficients related to a/L Te and a/L Ti respectively, while the 'residual' term, which is composed of the roto-diffusion term and other pure pinch terms, will be left out of our discussion. According to this equation, some important information can be obtained through scan over the normalized 5.…”
Section: Foot Regionmentioning
confidence: 99%
“…Comprehensive physics and engineering design for China Fusion Engineering Test Reactor (CFETR), with target fusion power of 1 GW and fusion gain Q > 10 to demonstrate tritium self-sufficiency and reactor relevant conditions, is underway [1]. The physics design covers a broad range of topics, such as improving the core plasma performance with optimization of heating and current drive [2,3], and evaluation of impurity effects on the CFETR fusion performance [4,5]. In the boundary, heat and particle exhaust solutions under conditions more severe than ITER are explored [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the neoclassical transport dominates over turbulent transport for W and neoclassical pinch of W causes its central accumulation. This could be understood as: in the region of ρ < 0.2 will enlarge the factor of poloidal asymmetries of heavy impurities, which could enhance the neoclassical transport of these species by several times, especially for the negative neoclassical convection [77][78][79][80][111][112][113][114][115][116][117].…”
Section: Simulated the Core W Transportmentioning
confidence: 99%
“…(a) Background turbulence (neoclassical transport) is weak (strong) in the ITB region (ρ < 0.4) as shown in figures 16 and 18, and ITG turbulent mode is the dominant mode as can be seen in figure16and reference[58]. These are not beneficial for removing core heavy impurities[79,80,[111][112][113][114][115][116][117] by increasing the turbulent diffusion. (b) Peaked main ion profile (n D ) mainly contributed by beam particle source (figures 9 and 11) will lead to the large negative neoclassical convection [77-80, 111-117].…”
mentioning
confidence: 99%
See 1 more Smart Citation